Enhancing Islamic Character and Religious Understanding Among Elementary Students Through Holiday Programs - Abdussomad Abdussomad (Yayasan Cerdas Pedia Indonesia, 2026)
The decline of religious literacy and moral character among elementary school children during holidays due to gadget addiction represents a crucial problem. This community service research aims to engineer an educational ecosystem to mitigate this degradation. Utilizing a combination of Participatory Action Research and Asset Based Community Development methods, the program capitalizes on classical curricula and boarding facilities. The intervention successfully involved exactly 32 children through a Total Immersion approach for five full days. Comprehensive evaluation shows highly significant results; 85% of participants successfully mastered recitation independently, while 100% demonstrated absolute reduction in gadget dependence and autonomously internalized worship discipline. These results clearly prove that experiential learning and milieu therapy surpass the effectiveness of conventional past programs. Habituation transition is guaranteed through parental involvement using daily monitoring instruments. In conclusion, this social engineering model is perfectly validated as a reliable social buffer to ensure continuous Islamic character sustainability for children.